If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 6) = 24 Reorder the terms: 2(6 + y) = 24 (6 * 2 + y * 2) = 24 (12 + 2y) = 24 Solving 12 + 2y = 24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2y = 24 + -12 Combine like terms: 12 + -12 = 0 0 + 2y = 24 + -12 2y = 24 + -12 Combine like terms: 24 + -12 = 12 2y = 12 Divide each side by '2'. y = 6 Simplifying y = 6
| x+10=4x+1 | | -282-(+1,017)=? | | 2y+48=8 | | M^2-6=5m | | f(x)=25x+150 | | 141-6x=30x+21 | | 28+2x=6x | | 10x+4=29 | | -4.9t^2+19.6t+58.8=0 | | 6(y-5)=-6 | | 5(y+3)=55 | | b^2-4*b+4=0 | | 8x-32=18+6x | | 2x+8-4x-15=16+8x-2-3 | | (3x+6)= | | y=(3x/12)+105 | | 2(x-6)+3x=8 | | 3x+30=90 | | (x^2+2x+1)(x^2+5x+4)=0 | | y=3x/12+105 | | 18-2x=2x+2 | | (y+5)(y^2-5y+25)= | | 1+6x-3x=19 | | 3x+35=13x-56 | | 4*1/2-1/3 | | 6x+17=65+3x | | (3x+30)= | | (x+-7)(x+-7)=14x | | 2(a-2)=-(a-1)/(a-4) | | X^2(5x+3)=26x | | 4x-4=2x+14 | | 1/3+2x=5/12 |